New Directions in Jewellery II - Cheung, Lin; Clarke, Beccy; Clarke, Indigo (London : Black Dog Publishing Limited, 2006)
Bak, Kirsten ; Bauer, Ela ; Blyfield, Julie ; Buescher, Sebastian ; Fritsch, Karl ; Schreiber, Constanze ; Broadhead, Maisie ; Bronger, Sigurd ; Hash, Arthur ; Isaac, Craig ; van der Leest, Felieke ; Mann, Lindsey ; Monzó, Marc ; Nadir, Noa ; Noten, Ted ; Alleweireldt, An ; Bodemer, Iris ; Fleischer, Silke ; Lee, Dongchun ; Nuis, Carla ; Sarneel, Lucy ; Seufert, Karin ; Truman, Catherine ; Walker, Lisa ; Zanella, Annamaria ; Besems, Dinie ; Brugger, Monika ; Furness, Madeleine ; Lingham, Rheanna ; El Odeh, Husam ; Parbs, Tiffany ; Thakker, Salima ; Bartley, Roseanne ; van Joolingen, Machteld ; Milheiro, Teresa ; Pierce, Shari ; Prins, Katja ; Willemstijn, Francis ; Bilenker, Melanie ; Buck, Kim ; Cheung, Lin ; Chilton, Cassandra ; Deville, Julia ; Hooper, Rory ; Mustonen, Eija ; Turner, Julia
Schenking Flanders DC
boek